WSN based intruder detection system based on Territorial Predator Scent Marking Algorithm (TPSMA) sensor node placement scheme - Abidin H.Z.; Subhamaniam S.R.; Din N.M.; Radzi N.A.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer hardware; Costs; Energy utilization; Hardware; Industrial electronics; Intrusion detection; Reconfigurable hardware; Sensor nodes; Zigbee; experimental; Intruder detection; Sensor node placement; TPSMA; validation; Wireless sensor networks